A Novel Method to Prevent Migration of Gastric Stent - Singla, Vikas; Khare, Shivam; Arora, Anil; Anikhindi, Shrihari Anil (Journal of Digestive Endoscopy, 2020)
Self expandable metal stent (SEMS) are widely used in patients with gastric outlet obstruction. Stent migration can occur in these patients, and is an important issue, which needs to be addressed. We used a novel technique for prevention of migration of gastric stent in an 80 year old female. Patient presented with recurrent vomiting due to gastric outlet obstruction by a growth in the antrum. SEMS was placed for palliation of symptoms. A nylon thread multiloop and through the scope clips were used to fix the SEMS with the gastric wall. The technique was used successfully to prevent the migration of SEMS.
Keywords: gastric outlet obstruction; migration; self-expandable metal stent